T cells and protective immunity to Plasmodium berghei in rats. - Brown, K N (1976)
Experiments were carried out in which unfractionated spleen cells, and T lymphocyte subpopulations characterized by certain experimental criteria, were isolated at various times from rats infected with Plasmodium berghei. By adoptive transfer it was shown that unfractionated spleen cells, and T cells alone, could transfer protection to syngenic recipients as early as 11 days after infection of the cell donors. The protection conferred by T cells increased with the duration of the infection in the donors, at least up to 100 days. The additional presence of B cells in transferred lymphocyte populations enhanced their protective capacity over that shown by T cells alone. The role of T cells in protective immunity to malaria is discussed.